Integrating Authentic Materials And Digital Resources To Enhance Efl Learners' Communicative Competence In Higher Education (Eurasian Journal of Learning and Academic Teaching, 2025)
This study examines the impact of integrating authentic materials and digital resources into English as a Foreign Language (EFL) instruction within higher education settings. Employing an experimental design, 60 university students participated over 12 weeks, divided into an experimental group exposed to authentic and digital resources and a control group following traditional textbook methods. Data collected through standardized pre- and post-assessments, questionnaires, and reflective journals suggest that the experimental group significantly outperformed controls in speaking, writing, motivation, and intercultural awareness measures. The findings support the hypothesis that blending authentic materials and digital tools fosters active engagement, improves communicative competence, and prepares learners for real-world communication challenges. The article concludes with pedagogical implications and recommendations for integrating these resources effectively in higher education contexts.